Malondialdehyde and carbonyl levels in skeletal muscle tissues after intermittent hypobaric hypoxia exposures - Syarifah Dewi; Alexander Rafael Satyadharma; Albertus Raditya Danendra; Wardaya (Acta Biochimica Indonesiana)
Background: Hypobaric hypoxia is a state of decreased oxygen pressure at high altitudes that can lead to hypoxia and oxidative stress as a result. Skeletal muscle is one of the important organs that can be affected by oxidative stress and cause contractile dysfunction.